Thermal, chemical and mechanical characterization of Azadirachta indica tree gum - Joy Mathavan, J.; Hassan, M.H. (Industrial Crops & Products, 2024)
This study focuses on the comprehensive thermal, chemical, and mechanical characterization of neem gum, a natural, colorless, tasteless polysaccharide obtained from Azadirachta indica tree’s trunk. The collection process of gum involves manual extraction from crude neem tree exudates, followed by thorough cleaning and ho mogenization with water. A portion of the resulting gum is then filtered, allowed to thicken, and naturally dried for subsequent mechanical testing. Various analytical techniques, such as thermogravimetric analysis (TGA), and differential scanning calorimetry (DSC) to determine the thermal properties, Fourier transform infrared spec trometry (FTIR) to find the functional groups, scanning electron microscopy (SEM), and micro-X-ray fluorescence analysis (µ-XRF) to decide the elemental composition, microhardness, tensile, flexural, and compression tests to determine the mechanical properties, are employed in this study. The thermal and mechanical properties of neem gum have been relatively unexplored, and this highlights the novelty and importance of this research. The results are analyzed and compared with other natural tree gums. The pH of 5.07 shows that the gum is slightly acidic in nature, and the peaks obtained from thermal analysis demonstrate that it doesn’t have a melting point. The microhardness value, tensile strength, flexural strength, and compressive strength of neem gum are 238.64 MPa, 1.0155 MPa, 1.899 MPa, and 1.1023 MPa, respectively. This research provides valuable insights into the diverse characteristics and potential applications of neem gum in various fields. It is being used in the pharmaceutical industry. It can also be used as a cap for cutting tools, such as drill bits, after manufacturing, during trans portation to protect their sharp edges from damage.
Keywords: Azadirachta indica tree gum; Mechanical properties; Fourier transform infra-red spectrum; μ X-ray fluorescence test; Simultaneous thermal analysis